Mediated-reality magnification for macular degeneration rehabilitation - Martin-Gonzalez, Anabel; Kotliar, Konstantin; Rios-Martinez, Jorge; Lanzl, Ines; Navab, Nassir (Journal of Modern Optics, 2014)
Age-related macular degeneration (AMD) is a gradually progressive eye condition, which is one of the leading causes of blindness and low vision in the Western world. Prevailing optical visual aids compensate part of the lost visual function, but omitting helpful complementary information. This paper proposes an efficient magnification technique, which can be implemented on a head-mounted display, for improving vision of patients with AMD, by preserving global information of the scene. Performance of the magnification approach is evaluated by simulating central vision loss in normally sighted subjects. Visual perception was measured as a function of text reading speed and map route following speed. Statistical analysis of experimental results suggests that our magnification method improves reading speed 1.2 times and spatial orientation to find routes on a map 1.5 times compared to a conventional magnification approach, being capable to enhance peripheral vision of AMD subjects along with their life quality. © 2014 © 2014 Taylor & Francis.
CRIS-Team Scopus Importer:2023-03-08
Keywords: age-related macular degeneration; central vision loss; head-mounted display; low vision rehabilitation; mediated reality